The Role of Penicillium Digitatum in Production of Single Cell Proteins from Citrus Reticulablanca Peels - Ullah Khattak, Hamad; Mehmood Ahmad, Sahibzada; Zulfiqar, Shandana; Tayyeb, Muhammad; Khan, Muhammad Junaid; Khattak, Aibad Ullah (ADVANCES IN BASIC MEDICAL SCIENCES, 2021)
Objective The potential use of kinnow peels as a substrate for Penicillium digitatum to manufacture single-cell protein was investigated in this work. Methodology Sulfuric acid in concentrations of 0.15, 0.30, and 0.45 N were used to pre-treat the substrate. The kinnow peels hydrolysate (KPH) medium and glucose supplemented kinnow peels hydrolysate medium were employed in this study. Results Kinnow peels hydrolysate produced 2.28%, 2.23%, and 2.07% crude protein at 0.15, 0.30, and 0.45 N per 20g of substrate utilized, respectively. Furthermore, on supplemented kinnow peels hydrolysate medium with inorganic nitrogen sources at 0.15, 0.30, and 0.45 N, the percentage of protein in single-cell protein was only 2.00%, 2.04%, and 2.15%, respectively. At 0.15, 0.30, and 0.45N, glucose was added to the augmented kinnow peels hydrolysate medium, yielding 2.12%, 2.02%, and 2.12%, respectively. Conclusion There was no effect of digestion normalities in case of KPH. The effect of normalities was noted when kinnow peels digest was supplemented with glucose. There was a decreasing trend in SCP production with an increase in normalities. No effect was noted when KPH was combined with M.M and glucose. Keywords Single Cell Proteins, Hydrolysate, Penicillium digitatum, KPH, Amino Acids, kinnow peels